Optimized design and development of a vehicle-mounted vertical axis wind turbine for defense cut-off locations and its performance analysis - Priyadharsini, M.; Gupta, Sunil Kumar; Gupta, Manoj (Institute of Advanced Engineering and Science, 2025)
This paper presents a vehicle-mounted vertical-axis wind turbine (VAWT) designed to generate power in motion and at cut-off locations. Particularly, its application to military vehicles is explored to provide uninterrupted electrical power for radio communication equipment and lighting needs in remote areas. The design uses a helical wind turbine for its compactness, lightweight, and suitability for vehicle mounting without heavy support structures. These turbines have low starting wind speeds, minimal vibration, portability, affordability, and low maintenance requirements. Utilizing fiberglass blades, the turbine unit measures 103 mm in height and 27.5 mm in diameter, achieving optimal rpm and torque for given wind speeds. Operating within the wind speed range of 10 km/h to 40 km/h, the VAWT produces an output voltage ranging from 5 V to 55 V, with a maximum wind turbine power output of 1120 watts at a wind speed of 12 m/s. The final generator output power obtained with the above wind turbine output of 1120 watts is 352 watts. A prototype unit has been tested and mounted on an all-terrain vehicle for evaluation. The paper provides detailed design steps, calculations, and insights for optimizing performance and facilitating large-scale implementation in the future.